Preservation of sexual and reproductive function in the treatment of extragonadal yolk sac tumors in the female genital tract - Ma, Xiao; Cao, Dongyan; Peng, Peng; Xiao, Yu; Yang, Jiaxin; Huang, Huifang; Zhang, Ying; Yu, Mei; Wang, Jinhui; Zhou, Huimei; Cheng, Ninghai; Wang, Tao; et al. (Frontiers in Pediatrics, 2022)
Objective: This study aimed to summarize the clinical features, treatment modalities, therapeutic effects, menstruation and fertility outcomes, and prognosis of extragonadal yolk sac tumors (YSTs) of the female genital tract. Methods: We reviewed 32 cases of extragonadal YSTs in the genital tract treated between 1983 and 2021. The medical records, including clinical characteristics, histopathology, treatments, chemo-reduced adverse events, and outcomes on long-term follow-up, were collected. Results: Among the 32 cases, there were 30 cases of vaginal YSTs and two cases of uterine YSTs (endometrial and cervical). Thirty patients (30/32, 93.8%) were <4 years of age. Abnormal vaginal bleeding (n=31) and elevated serum alpha-fetoprotein level (n=32) were the most common presentations. Vaginohysteroscopy and/or pediatric rhinoscopy were used for diagnosis in 17 pediatric patients and evaluation of chemotherapeutic efficacy in 21 pediatric patients. All patients received combination chemotherapy. Bleomycin/etoposide/cisplatin (BEP) was selected with prior consideration in 28 cases; 21 patients were treated with BEP alone. Yellow or grayish-yellow tissue with an irregular shape was found in 66.7% of the cases during repeat examinations. Five patients underwent surgeries during repeat examinations and follow-ups, and no evidence of malignancy was noted in them. Thirty-one patients achieved complete remission. During a median follow-up of 63 months (2.4–240.3 months), two patients experienced recurrence, three died, and 29 remained disease-free. One patient recovered menstruation and five had undergone menarche. Conclusions: BEP chemotherapy can serve as a preferred treatment modality for vaginal and uterine YSTs. Vaginohysteroscopy and pediatric rhinoscopy can be used for the diagnosis and evaluation of chemotherapeutic efficacy in pediatric patients. YSTs possibly appear as yellow or grayish-yellow after chemotherapy.